Australian GP management of osteoarthritis following the release of the RACGP guideline for the non-surgical management of hip and knee osteoarthritis. (December 2015) - Basedow, Martin; Williams, Helena; Shanahan, E.; Runciman, William; Esterman, Adrian
Abstract Background Osteoarthritis (OA) is a highly disabling and costly condition with an escalating prevalence in Australia due to the ageing and increasing obesity of the population. The general practitioner (GP) plays a central role in the management of this condition. The aim of this study was to examine opinions about the management of OA by Australian GPs following the release of the Royal Australian College of General Practitioners Guideline for the non-surgical management of hip and knee OA (RACGP OA CPG), and to compare the results with an earlier survey administered by the National Prescribing Service. Methods In January 2013, a self-administered questionnaire was sent to 228 GPs to determine their treatment approaches to OA management using a clinical vignette of a patient with OA. This was compared with results from a similar survey undertaken in 2006. Results Seventy-nine GPs returned questionnaires (response rate 35 %). GP recommendations for paracetamol, a paracetamol/codeine compound, and oral non-steroidal anti-inflammatory drugs (NSAIDs) were consistent with recommendations in the RACGP OA CPG, and varied little from the previous survey. Notably, there was a marked increase between surveys in GP recommendations for tramadol (p = 0.004) and more potent opioids (p < 0.001). Advice about the adverse effects of NSAIDs and codeine and how to manage them increased between surveys (p = 0.038 and 0.005, respectively). For all non-pharmacological treatments, there were only minor changes in the percentage of GP recommendations when compared with the previous survey, however they remain underutilised. Conclusions GPs generally demonstrated a conservative approach to the treatment of OA, however, the increased recommendations for more potent opioids warrants further investigation. Patients should be made aware of the risks of medications through the use of decision aids, which can provide structured guidance to treatment. Non-pharmacological interventions were not given the importance that is suggested by clinical practice guidelines.